2005
DOI: 10.1074/jbc.m411412200
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein AV Accelerates Plasma Hydrolysis of Triglyceriderich Lipoproteins by Interaction with Proteoglycan-bound Lipoprotein Lipase

Abstract: Apolipoprotein A5 (APOA5) is associated with differences in triglyceride levels and familial combined hyperlipidemia. In genetically engineered mice, apoAV plasma levels are inversely correlated with plasma triglycerides. To elucidate the mechanism by which apoAV influences plasma triglycerides, metabolic studies and in vitro assays resembling physiological conditions were performed. In human APOA5 transgenic mice (hAPOA5tr), catabolism of chylomicrons and very low density lipoprotein (VLDL) was accelerated du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
69
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(75 citation statements)
references
References 33 publications
6
69
0
Order By: Relevance
“…By contrast, apoC-II had a major stimulatory effect on LPL activity. Importantly, in support of our findings, Merkel et al (16) recently reported that apoA-V did not affect LPL hydrolysis rates in the absence of proteoglycans. Thus, although a clear explanation for the different results is not available at present, it is conceivable that, under certain incubation conditions, apoA-V may alter the substrate emulsion, thereby increasing TG accessibility and LPL activity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…By contrast, apoC-II had a major stimulatory effect on LPL activity. Importantly, in support of our findings, Merkel et al (16) recently reported that apoA-V did not affect LPL hydrolysis rates in the absence of proteoglycans. Thus, although a clear explanation for the different results is not available at present, it is conceivable that, under certain incubation conditions, apoA-V may alter the substrate emulsion, thereby increasing TG accessibility and LPL activity.…”
Section: Discussionsupporting
confidence: 80%
“…Subsequent interaction studies with chylomicrons revealed that prior enrichment with apoA-V results in an increased binding. These studies, which provide direct evidence that ternary interactions between LPL, TG-rich lipoprotein, and heparin are enhanced in the presence of apoA-V, are congruent with the recent findings of Merkel et al (16) who showed that proteoglycan-bound LPL activity is modulated by apoA-V. Attempts to demonstrate the release of cell surface heparan sulfate proteoglycan-associated apoA-V upon injection of heparin into human volunteers, however, failed to show an affect.…”
Section: Discussionsupporting
confidence: 76%
“…Lookene et al (13) showed that apoA-V binds to heparin and facilitates binding of chylomicrons and VLDL to heparin by bridging the lipoproteins to the glycan chains. In accordance, Merkel et al found that apoA-V stimulates lipolysis when the lipase is bound to heparan sulfate proteoglycans on microtiter plates (9).…”
mentioning
confidence: 51%
“…not incorporated into lipoproteins) could compete with the binding to the arterial wall and prevent arteriosclerosis. In addition, lipoprotein lipase binds to proteoglycans (62). Thus, lipoprotein lipase could be bound to lipoproteins with the involvement of the chondroitin sulfate chain of apoO.…”
Section: Discussionmentioning
confidence: 99%